RELATIONSHIP BETWEEN THE DEGENERATIVE CHANGES IN THE MANDIBULAR CONDYLE AND ARTICULAR EMINENCE INCLINATION, HEIGHT, AND SHAPE: A CBCT STUDY - Seçil Aksoy; Hakan Kurt; Cansu Görürgöz; Çiğdem Şeker; Murat İçen; Kaan Orhan (Cumhuriyet University, 2022)
Objectives: This study aimed to analyze the articular eminence inclination and height and correlate these findings with the eminence shapes and degenerative condylar changes using cone-beam computed tomography (CBCT). Materials and Methods: The assessments were established on CBCT images of 566 temporomandibular joints (TMJ) that were included from the computer database. Age and gender were recorded for all individuals. Degenerative changes were examined in the articular surface of the condyle. The articular eminence (AE) inclination and height measurements were performed on central parasagittal slices of the TMJ. The shape of the AE was classified as box, sigmoid, flattened, and deformed. Results: The prevalence of degenerative changes in the condyle was higher in males, but no significant difference was found (p ˃ 0.05). The AE inclination and height have a relation with gender and age groups. The AE inclination and height results were greater in males (p < 0.05). The reduced mean values of eminence inclination and height in the +50-year-old group were detected (p < 0.05). Sigmoid and box-shaped articular eminence morphologies were more common. The eminence with deformed-shaped was related to two or more degenerative alterations in the condylar head. Conclusion: The degenerative condylar changes can affect eminence inclination and height by mechanical loading and changed articular dynamics. Gender and age have a significant effect on the AE morphology. The articular eminence shape is influenced by combinations of two or more degenerative changes.